Aggregate implications of corporate bond holdings by nonfinancial firms - Miguel H. Ferreira (Queen Mary University of London, School of Economics and Finance, 2023)
This paper explores the impact of risky asset holdings by U.S. nonfinancial firms. From the early 1990s to 2017, the share of risky securities surged from 28% to over 40% of firms' financial assets. Using a business-cycle heterogeneous firms model, I show that declining real interest rates since the 1980s increased the risk premium, driving the increase in risky asset holdings. The model predicts that firms with higher exposure to risky assets experience an investment decline up to 50% more pronounced during large shocks, empirically validated by analyzing the Great Financial Crisis.
Keywords: E22; E44; G11; 330; Risky assets; corporate bonds; firm heterogeneity; firm dynamics; business-cycle